2018
DOI: 10.1021/acs.jctc.8b00377
|View full text |Cite
|
Sign up to set email alerts
|

Building Blocks of the Outer Membrane: Calculating a General Elastic Energy Model for β-Barrel Membrane Proteins

Abstract: The outer membranes of Gram negative bacteria are the first points of contact these organisms make with their environment. Understanding how composition determines the mechanical properties of this essential barrier is of paramount importance. Therefore, we developed a new computational method to measure the elasticity of transmembrane proteins found in the outer membrane. Using all-atom molecular dynamics simulations of these proteins, we apply a set of external forces to mechanically stress the transmembrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 61 publications
2
23
1
Order By: Relevance
“…Given the high disorder and slower folding of the secretome (Tsirigotaki et al, 2018), it is unsurprising that specific evolutionary adaptations are needed to secure that its polypeptides can acquire their final folded states. Enhanced secretome native state thermostability (Figure 2B, VI; Leuenberger et al, 2017; Mateus et al, 2018) may compensate for the elevated dynamics of the folding intermediates, while stability of native OM proteins comes from the lipid-embedded state (Lessen et al, 2018). In addition, up to a third of native states in secretome polypeptides are stabilized by disulfides (Supplementary Table S3), oligomerization (e.g., HdeA, PhoA, Spy, CsgA, Lpp), metal ion binding (e.g., Ca 2+ , glucose binding protein; Herman et al, 2005) and prosthetic groups (e.g., the cytochrome c-type protein NrfB; Clarke et al, 2007) and many other solutions (De Geyter et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Given the high disorder and slower folding of the secretome (Tsirigotaki et al, 2018), it is unsurprising that specific evolutionary adaptations are needed to secure that its polypeptides can acquire their final folded states. Enhanced secretome native state thermostability (Figure 2B, VI; Leuenberger et al, 2017; Mateus et al, 2018) may compensate for the elevated dynamics of the folding intermediates, while stability of native OM proteins comes from the lipid-embedded state (Lessen et al, 2018). In addition, up to a third of native states in secretome polypeptides are stabilized by disulfides (Supplementary Table S3), oligomerization (e.g., HdeA, PhoA, Spy, CsgA, Lpp), metal ion binding (e.g., Ca 2+ , glucose binding protein; Herman et al, 2005) and prosthetic groups (e.g., the cytochrome c-type protein NrfB; Clarke et al, 2007) and many other solutions (De Geyter et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Atomistic simulations of different OMPs embedded in a DMPC bilayer and subject to external forces, have been applied to derive an elastic energy model for OMPs, in which specific features of the barrel structure allow OMPs to withstand stress, possibly contributing the structural stability of the OM. 497 The calculation of area compressibility from atomistic simulations of different models of the OM and the IM as well as of a model of the cell wall have linked elastic properties of lipid and protein components to the mechanical properties of the envelope as a whole. 498 This type of studies provides a framework where structural properties of lipids and proteins are related to macroscopic features of the cell envelope.…”
Section: Outer Membrane Proteinsmentioning
confidence: 99%
“…Although the familiar fluid-mosaic model of membranes found in most textbooks depicts a biological membrane with just a few proteins floating in a “sea” of lipid, the OM is markedly different, containing instead a much higher fraction of protein by weight, with lipid/protein ratios (LPRs) (w/w) estimated to be between 0.14 and 0.36 ( 139 , 156 ), corresponding to only 2–4 LPS and 4–10 phospholipid molecules per OMP ( 157 ). Estimates based on biochemical studies suggest that as much as 50% of the surface area of the OM may be occupied by OMPs ( 7 ), whereas AFM studies ( 156 ) ( Fig.…”
Section: Another Brick In the Wall: Building The Ommentioning
confidence: 99%
“…On this point, an abundance of clustered OMPs with low mobility may make the OM locally rigid. Indeed, molecular dynamics (MD) simulations have shown that membranes containing 8–12-stranded OMPs are much stiffer than membranes containing only DMPC ( di C 14:0 PC) ( 157 ). However, simulations investigating larger length scales have shown that crowding a bilayer with some OMPs ( i.e.…”
Section: Another Brick In the Wall: Building The Ommentioning
confidence: 99%
See 1 more Smart Citation